iSCAT microscopy and particle tracking with tailored spatial coherence - Mazaheri, Mahdi; Kasaian, Kiarash; Albrecht, David; Renger, Jan; Utikal, Tobias; Holler, Cornelia; Sandoghdar, Vahid (Optica, 2024)
Interferometric scattering (iSCAT) microscopy has demonstrated unparalleled performance among label-free optical methods for detecting and imaging isolated nanoparticles and molecules. However, when imaging complex structures such as biological cells, the superposition of the scattering fields from different locations of the sample leads to a speckle-like background, posing a significant challenge in deciphering fine features. Here, we show that by controlling the spatial coherence of the illumination, one can eliminate the spurious speckle without sacrificing sensitivity. We demonstrate this approach by positioning a rotating diffuser coupled with an adjustable lens and an iris in the illumination path. We report on imaging at a high frame rate of 25 kHz and across a large field of view of 100 µm × 100 µm, while maintaining diffraction-limited resolution. We showcase the advantages of these features by three-dimensional (3D) tracking over 1000 vesicles in a single COS-7 cell and by imaging the dynamics of the endoplasmic reticulum (ER) network. Our approach opens the door to the combination of label-free imaging, sensitive detection, and 3D high-speed tracking using wide-field iSCAT microscopy.
CRIS-Team Scopus Importer:2024-08-02